Performance Analysis of Certified Teachers at Budi Satrya High School - Meha, Yusnia; Fadhli, Muhammad (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This research aims to analyze the performance of certified teachers at Budi Satrya High School with a focus on evaluating teaching quality, interaction with students, and contribution to student learning. The research method used is a case study with a qualitative approach, this research is included in the category of descriptive research or exploratory study. This research uses qualitative techniques involving school principals and certified teachers. Data was collected through school observations, interviews with teachers, and analysis of related documents. The research results show that the role of the principal in improving the performance of certified teachers at Budi Satrya High School is by providing motivation, providing supervision to teachers, establishing effective communication and increasing collaboration between certified and non-certified teachers. Furthermore, there are strategies for certified teachers in improving their performance at Budi Satrya High School, namely certified teachers plan quality learning, certified teachers also integrate technology into the learning process and finally certified teachers support every academic and non-academic activity at Budi Satrya High School to further improve their performance.Keywords : Teacher Performance; Certification